Churn analysis. (Fighting churn., 2022)
In this video, Carl Gold explains module number 4: Feature Engineering. The objective of this milestone is: - Your boss at Manning looks at the results and thinks they're really good. But they want you to look into a few more things to see if different views of the customer help you understand churn. - Your boss suggests the following additional customer metrics that they want you to create and see how they relate to churn using the techniques from the previous milestones. * The total number of customer events in the last 90 days * The number of distinct products the customer used in the last 90 days * The total number of actions related to browsing free content * Total number of actions related to enhanced reading features * The percentage of actions that include reading an owned book * The number of downloads the customer makes per unique product.